Cramer’s Rule: Other Example

(1) Solve by Cramer’s Rule
x + 3y + z = 14
2x + y + 4z = 5
5x – y + 3z = –12

(Ans. x = –2, y = 5, z = 1)

 

(2) Solve by Cramer’s Rule
x + 2y + 3z = 6
3x + 2y – 2z = 3
2x – y + z = 2

(Ans. x = 1, y = –5, z = –5)

(3) Solve by Cramer’s Rule
x – 3y + 4z = 3
2x – 5y + 7z = 6
3x – 8y + 11z = 11

(4) Solve by Cramer’s Rule
x + 3y = 7
2x + 6y = 11
(5) Solve by Cramer’s Rule
x – y + 3z = 6
x + 3y – 3z = –4
5x + 3y + 3z = 10

(Ans. x = 7–3k/2, y = 3k–5/2, z = k)

Leave a Reply

Your email address will not be published. Required fields are marked *